Inovasi Metode Pembelajaran Kolaboratif di Era digital: Studi Kasus Perguruan Tinggi Swasta Magetan: Innovation of Collaborative Learning Methods in the Digital Era: Case Study of Magetan Private Colleges - Arum Putri Rahayu; Hernik Khoirun Nisak; Samuji; Ahmad Wahib; Anam Besari (ITScience (Information Technology and Science), 2024)
The importance of innovation in learning methods cannot be ignored, especially in the digital era where access to information is very easy. Collaborative learning methods have been shown to increase student engagement and understanding. This study evaluates the implementation of collaborative learning methods in three private universities in Magetan, namely Universitas Doktor Nugroho and STAI Ma'arif Magetan, using a quantitative survey method. The study shows that collaborative learning methods are effective in increasing student understanding and engagement. Technology plays an important role in supporting collaborative learning with very high usage, although infrastructure support still needs to be improved. The role of lecturers is very significant in facilitating collaborative learning, and student satisfaction with this method is high. However, there are still moderate obstacles in implementing this method. In addition, collaborative learning methods show a positive impact on student academic achievement. To improve the effectiveness of collaborative learning, it is necessary to improve infrastructure support and training for lecturers and the implementation of innovative teaching strategies. This study provides recommendations for further development in the implementation of collaborative learning methods in universities, especially in the context of technology use and improving the overall quality of education.